The Impact of Very Short-term Variability of Blood Pressure in Outcome after Successful Thrombectomy - Francisca Isabel Barros Ferreira (2020)
Background and Purpose: We aim to determine if the very short-term blood pressure variability (BPV) after successful endovascular treatment of acute ischemic stroke has a relevant impact in the clinical outcome. Methods: This is a prospective multicenter study with inclusion of consecutive AIS patients with occlusion of intracranial anterior circulation vessels who achieved successful recanalization (modified Treatment In Cerebral Ischemia grades 2b-3) after thrombectomy. Very short-term BPV was assessed by spectral analysis of spontaneous fluctuations of beat-to-beat systolic blood pressure values recorded by finger plethysmography with Finometer device. Outcomes included independence at 90 days (modified Rankin scale 0-2) and the initial clinical response to mechanical thrombectomy. Results: We included 121 patients. Increased BPV at high frequencies (rapid oscillations) was independently associated with poor functional outcome at 90 days (normalized units, odds ratio (OR) = 0.56, 95% confidence interval (CI) 0.35 - 0.88, p=0.01; low/high frequency ratio OR = 1.38, CI 1.09 - 1.76, p<0.01) and early neurological recovery (normalized units, OR = 0.67, CI 0.46 - 0.98, p=0.04) in multivariate analysis. Conclusions: The magnitude of rapid oscillations of blood pressure has a significant impact in early neurological recovery and late functional outcome of ischemic stroke patients after successful recanalization. Very short-term BPV can be assessed quickly throughout the post intervention period and potentially contribute to a more efficient blood pressure control in AIS patients submitted to endovascular treatment.